2014
DOI: 10.4183/aeb.2014.84
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin and Glycemic Profiles in Type 2 Diabetes Patients on Eicosapentaenoic Acid with or without Vitamin E

Abstract: Background. Secreting different adipocytokines, adipose tissue plays an important role in health and disease. Upon omega-3 consumption, changes in the secretion of adipose tissue and its effects on glycemic profile are a controversial subject at the present time.Objectives. We evaluated the effects of eicosapentaenoic acid (EPA) alone and in combination with vitamin E on adiponectin and serum glycemic indices in type II Diabetes patients.Design. This double-blind clinical trial divided all patients randomly in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…After applying all the selection criteria, 15 studies were included in the systematic review [ 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ]. These studies reported the following outcomes: plasminogen-activator inhibitor 1 (PAI-1), adiponectin, leptin, resistin, tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After applying all the selection criteria, 15 studies were included in the systematic review [ 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 ]. These studies reported the following outcomes: plasminogen-activator inhibitor 1 (PAI-1), adiponectin, leptin, resistin, tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6).…”
Section: Resultsmentioning
confidence: 99%
“…These studies reported the following outcomes: plasminogen-activator inhibitor 1 (PAI-1), adiponectin, leptin, resistin, tumor necrosis factor α (TNF-α), and interleukin 6 (IL-6). One study [ 42 ] had a cross-over design, and could not be included in the quantitative synthesis (meta-analysis) in Review Manager; hence, 14 studies with parallel design were included in the meta-analysis [ 30 31 32 33 34 35 36 37 38 39 40 41 43 44 ]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two groups contained 23 patients each and were considered statistically similar in terms of demographic features and of associated comorbidities, such as metabolic syndrome and diabetes which might have had an impact over adiponectin values (18).…”
Section: Presentation Of the Study Groupsmentioning
confidence: 99%
“…Some studies showed that vitamin E supplementation improves glycemic indices and insulin resistance in patients with T2DM from Western and Asian countries [10][11][12][13], while other studies from these regions did not report such a significant effect on patients with diabetic nephropathy [14][15][16] and T2DM patients [17][18][19]. In contrast, some studies indicated a significant increase in the blood glucose level following vitamin E supplementation among Asian patients with T2DM [20,21]. In a meta-analysis of RCTs in 2014, Xu et al reported that vitamin E supplementation did not result in significant benefits in glycemic control, as measured by glycated hemoglobin (HbA1c), and fasting insulin, among patients with T2DM [22].…”
Section: Introductionmentioning
confidence: 99%